Vitamin D in bovine health and pathologies: a non-classical approach - Tiraboschi, Georgina (2023)
Vitamin D is a fat-soluble vitamin of relevance for dairy cattle, which is not only involved in calcium homeostasis and bone metabolism but has also been associated with the modulation of the immune system and a lower incidence of certain bovine pathologies. The latest actions of the secosteroid, referred to as non-classical, are of more recent discovery and are still under study. The objective of this bibliographic review was to present and analyse the roles of vitamin D and its metabolites in bovine health and pathologies. A section on immunomodulatory and antibacterial effects in the bovine mammary gland was included, where the vitamin and its precursors are known to decrease bacterial invasion and regulate the expression of components of the innate immune response. For purposes of contextualization, the metabolism of vitamin D, the source and quantification of its metabolites in bovine milk and plasma, its role in nutrition and disease prevention, as well as toxicity are also described. In conclusion, the study of the non-classical effects of these steroids provides evidence that can be used to design therapies with natural compounds to be applied in food-producing animals.